Paisajes sonoros del retorno palma de aceite, despojo y culturas de paz en el postconflicto colombiano - Ramírez Gröbli, María del Pilar (Nexos y Diferencias. Estudios de la Cultura de América Latina, 2020)
"This book presents a novel analysis of land conflicts arising from large-scale oil palm plantations in Colombia. The study reveals the powerful political dimension of music in the context of the country's transition The study addresses strategies, mechanisms and peace-building actions that peasant communities have undertaken to mobilize the processes of return to their territories, after having experienced the development of the Colombian oil palm monoculture in rural Colombia. forced displacement.